2013
DOI: 10.1002/jgrd.50195
|View full text |Cite
|
Sign up to set email alerts
|

Does laboratory‐scale physics obstruct the development of a theory for climate?

Abstract: [1] Despite best efforts, there still is no physical theory for climate based on the physics of the laboratory regime (i.e., fluid mechanics, radiative transfer, classical thermodynamics, etc.). This paper builds from previous discussions on how laboratory-regime assumptions may lock our current theoretical efforts into the laboratory regime and how we might get around this problem. Using ultralong time photographic exposures (known as solargraphs) for inspiration, it draws into question classical thinking abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Empirically based reports of validation failure in complex general-circulation models abound in the journals [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Most recently, Zhang et al [30] reported that some 93.4 % of altocumulus clouds observed by collocated CALIPSO and CloudSat satellites cannot be resolved by climate models with a grid resolution [1°(110 km).…”
Section: Empirical Evidence Of Models Running Hotmentioning
confidence: 99%
“…Empirically based reports of validation failure in complex general-circulation models abound in the journals [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Most recently, Zhang et al [30] reported that some 93.4 % of altocumulus clouds observed by collocated CALIPSO and CloudSat satellites cannot be resolved by climate models with a grid resolution [1°(110 km).…”
Section: Empirical Evidence Of Models Running Hotmentioning
confidence: 99%
“…Thus, the slow time results in [ 2 ], wherein temperature fails to exist because of heavy tails, are not physically problematic. However, they do raise concerns about existing physical models for slowly varying noisy processes such as climate and weather [ 9 , 10 , 11 ].…”
Section: No Temperature No State Function No Equilibriummentioning
confidence: 99%
“…When all of these vector fields are the same, there is one reference an observer could ride in where all currents stop. The term “generalized wind” was later coined to describe these vector fields [ 3 ]. When a single “generalized wind” velocity exists for all currents there exists a frame where no process occurs.…”
Section: Introductionmentioning
confidence: 99%